Vzdělávací soustava a jednota vědění - Tulka, Jiří (Univerzita Pardubice, 2001)
The idea of integrated learning can be viewed from man different stadpoints. In any case, it must rest against the demand for the integrity of the scientific system and for the integrity of the education of humankind. Although in this concept, the thought reaches far beyond the borders of the elementary school education programme. The 20th century is marked by an extraordinary growth in the knowledge of mutual relationships on different levels of the empirical entily ("the century of vertical integration"). This fact should become the basic of the construction of the final model of the general education. The author of the article strives to emphasise the key moments upon which the model characterised above should rest.
Keywords: vědění; vzdělávací systémy; poznání; historický vývoj